Studentų lituanistų mokslinė konferencija – tiltas, jungiantis lituanistus - Baranauskienė, Rita (Respectus Philologicus, 2025)
Conceived by Lithuanian language students at Vilnius University’s Faculty of Philology and organised since 2023 in collaboration with Kaunas University, the student conference General Rehearsal has already become a tradition, bringing together young researchers from two university faculties for the fifth year in a row and providing an opportunity to share scientific insights and discoveries and rehearse the defence of their work. The aim of the scientific conference is to provide students with an opportunity to present their scientific or research work, develop the competencies of future specialists in the humanities, and discuss the importance of philology in the 21st century.